The phenomenon of xenoglossophilia in podcast media: A portrait of generation Z’s communication - Wardani, Oktarina Puspita; Arsanti , Meilan; Chamalah , Evi; Wahyuningrum , Dwi Wara (BAHASTRA, 2025)
This study aims to analyze how xenoglossophilia manifests in podcast content, and its impact on the communication patterns of Generation Z. Adopting a qualitative approach, this study uses discourse analysis to examine popular podcasts that frequently incorporate foreign languages and are widely consumed by Generation Z. The survey results conclude that Generation Z's foreign language use is primarily driven by social trends and influences, with social media and films as the primary sources. Foreign languages are most frequently used in everyday conversation and social media, while usage in formal contexts remains low, suggesting that this practice is more of a lifestyle than a communicative need. Analysis of The Indah G Show podcast reinforces these findings through quotes highlighting the superiority of English over Indonesian in terms of efficiency and vocabulary. This phenomenon reflects a shift in the linguistic attitudes of the younger generation and poses challenges in maintaining the sustainability and prestige of the Indonesian language in the era of globalization. This study recommends the development of a digital media-based learning model for the use of foreign languages to preserve and strengthen national language identity.